Penerapan Hand and Minds On Activity Melalui Model CTL Pada Pembelajaran Fisika untuk Meningkatkan Kemampuan Keterampilan Proses Sains Siswa SMP - Ulina, Ninta Sri; Wahyuni, Sri Endang; Suharmanto, Puji; Putri, Aninditha Chintya (UNIVERSITAS INDRAPRASTA PGRI, 2024)
Science process skills have a very important role in the process of forming knowledge. Get students used to learning through scientific work processes, as well as practicing detailed scientific skills and systematic work. The aim of this research is to improve students' science process skills through the application of Hands and Minds On Activity with a Contextual Teaching and Learning approach. The method used is classroom action research. The aspect observed in this research is students' science process skills through description tests which are assessed in each cycle. Based on the research results, students' science process skills can be said to be successful, because the average student score increased from cycles I, II, and II where each cycle had a percentage of 68.0%, 73.9%, and 81.7 %. An increase in the value to 81,7% shows that the success indicators have been met. This is in accordance with the learning target which expects 80% of students to exceed the KKM limit at school.